LOSS AND RECOVERY OF NATIONALITY IN IRAQI LAW - Prof. Fadwa Al-kahwaji; Zeyad Tariq Ibrahim (American Journals, 2024)
This study aimed to clarify the provisions of loss and restoration of nationality in Iraqi legislation, by defining the nature of loss of nationality and the cases of loss and restoration of it, where the descriptive and analytical approach was relied upon, and the reason for the loss is due to the will of the individual, which is based on his freedom to change Iraqi nationality and obtain foreign nationality. Or the will of the state by stripping the person who acquired Iraqi citizenship of it or withdrawing his citizenship from the person concerned if the reasons for it are available. Losing Iraqi citizenship has special effects, and the recovery procedure according to Iraqi law is limited to those who had original Iraqi citizenship and lost it due to one of the reasons for the loss. Finally, we recommended that it was It would be better for the Iraqi legislator to stipulate residency in Iraq as a condition for the woman to regain her Iraqi nationality, which she renounced because she acquired the nationality of her foreign husband. This condition will undoubtedly work to re-instill the spirit of loyalty to the state and integration into Iraqi society after the end of the marital bond that required her to renounce her Iraqi nationality. Hence, its spirit of citizenship was weakened and its loyalty to the Iraqi state weakened.
Keywords: Loss of nationality, restoration of nationality, Iraqi Code of Procedure.